Qos Enhancement in Manet by Directional Power Control - Cakan, Tomas; Wieser, Vladimir; Tkac, Andrej (Communications - Scientific letters of the University of Zilina, 2014)
In this paper, the 4-Way Directional Power Control with Recoil Loop (4WDPCRL) protocol for power control of directional antennas is presented. We propose the scheme with using of control packets (RTS/CTS/DATA/ACK) for exchanging information about node’s transmitted energy. Whenever the frame is received, the appropriate power for transmitted frame is computed. This information is stored together with updated information about position of node to the table. If a new transmission occurs, the node sends packet with updated information about position and appropriate power. The simulation results show that the throughput and energy consumption of the proposed protocol was improved compared to IEEE 802.11 MAC protocol with omni-directional antenna and DMAC protocol with directional antenna.